Teaching History Through Gamification: A Motivating Methodology - Trejo Alarcón, Jorge Alejandro (2026)
The objective of the research described here was to use gamification as a teaching strategy to improve student motivation in the subject of Mexican History at Colegio Real Victoria in Veracruz during the 2023-2024 school year. The inquiry followed an experimental methodology and a mixed-methods approach, using surveys and observation as data collection techniques. Initially, the study population consisted of 60 students; however, after a pilot test, half were excluded, leaving only 30 fourth-semester students. The surveys were administered to the selected fourth-semester students in groups A and B and were structured around three dimensions: the importance of the subject, teaching strategies, and gamified motivation. The results show that the students consider the subject important and that the teaching strategies used may or may not motivate them. In conclusion, using gamification as a teaching strategy helps motivate students and improves formative and summative results.